A Review of Botany, Phytochemical, and Pharmacological Effects of Dysphania ambrosioides - Hewis, Lavisiony Gracius; Daeli, Giovanni Batista Christian; Tanoto, Kenjiro; Carlos, Carlos; Sahamastuti, Agnes Anania Triavika (Indonesian Journal of Life Sciences, 2020)
Traditional medicine is widely used worldwide due to its benefits and healthier components that these natural herbs provide. Natural products are substances produced or retrieved from living organisms found in nature and often can exert biological or pharmacological activity, thus making them a potential alternative for synthetic drugs. Natural products, especially plant-derived products, have been known to possess many beneficial effects and are widely used for the treatment of various diseases and conditions. Dysphania ambrosioides is classified as an annual or short-lived perennial herb commonly found in Central and South America with a strong aroma and a hairy characteristic. Major components in this herb are ascaridole, p-cymene, α-terpinene, terpinolene, carvacrol, and trans-isoascaridole. Active compounds isolated from this herb are found to exert various pharmacological effects including schistosomicidal, nematicidal, antimalarial, antileishmanial, cytotoxic, antibacterial, antiviral, antifungal, antioxidant, anticancer, and antibiotic modulatory activity. This review summarizes the phytochemical compounds found in the Dysphania ambrosioides, together with their pharmacological and toxicological effects.